Depression, anxiety, stress, and satisfaction with daily occupation among caregiver of elderly diabetic patient / Farrah Shafeera Ibrahim ... [et al.] - Ibrahim, Farrah Shafeera; Lintau, Stanley; Ilias, Kartini; Munianndy, Naleena Devi; S. A Saghir, Fatma; Mohd Natar, Ahmad Kamal (Universiti Teknologi MARA, Sabah, 2021)
A caregiver is a person who is taking care of a sick or dependent individual. The caregiving process would involve numerous tasks like helping the patients with daily activities, supervising medications, and arranging medical appointments. The demand and multiple roles as caregivers might lead them to experience depression, anxiety, and stress. The study aimed to evaluate the prevalence and relationship of depression, anxiety, stress, and satisfaction with daily occupation among the caregivers of elderly diabetic patients. This study adopted a cross-sectional design. A total of 139 participants who were the caregivers of elderly diabetic patients consented to participate in this study. The results indicated a low percentage of caregivers with a high level of depression, anxiety, and stress, and low level of satisfaction with daily occupation. There was a significant strong negative relationship between satisfaction with daily occupation with depression (r = -0.806), anxiety (r = -0.764), and stress (r = -0.770). The more complications of the patients have a significant fair, positive correlation with depression (r = 0.366), anxiety (r = 0.183), and stress (r = 0.384), with a fair negative correlation with satisfaction with daily occupation (r = -0.381) among the caregivers. The findings in this study might open the doors for supporting those caregivers. The positive correlation between depression, anxiety, and stress with complications of the patients that they are taking care of indicates that these caregivers need to be educated on self-care and techniques in coping stress.